1H, 13C and 15N backbone and side-chain chemical shift assignments for oxidized and reduced desulfothioredoxin - Garcin, Edwige B.; Bornet, Olivier; Pieulle, Laetitia; Guerlesquin, Françoise; Sebban-Kreuzer, Corinne (Biomolecular NMR assignments, 2010)
Based on sequence homology, desulfothioredoxin (DTrx) from Desulfovibrio vulgaris Hildenborough has been identified as a new member of the thioredoxin superfamily. Desulfothioredoxin (104 amino acids) contains a particular active site consensus sequence, CPHC probably correlated to the anaerobic metabolism of these bacteria. We report the full 1 H, 13 C and 15 N resonance assignments of the reduced and the oxidized form of desulfothioredoxin (DTrx). 2D and 3D heteronuclear NMR experiments were performed using uniformly 15 N-, 13 C-labelled DTrx. More than 98% backbone and 96% side-chain 1 H, 13 C and 15 N resonance assignments were obtained. (BMRB deposits with accession number 16712 and 16713).